Exploring Hurtt’s Professional Scepticism Scale for Accounting Students - Muhammad, Kamaruzzaman; Ghani, Erlane K.; Ilias, Azleen; Razali, Fazlida Mohd; Yassin, Nur Dafina Afiqah Mohd (International Review of Management and Marketing, 2024)
This study verifies that the scepticism scale devised by Hurtt (2010) for assessing the practical implementation of professional scepticism among university accounting students is appropriate, as supported by the auditing literature. On the basis of twenty-two modified items of Hurtt’s (2010) professional scepticism scale, 319 responses were gathered. Hurtt’s professional scepticism scale can be applied to accounting students, according to the findings. Notwithstanding variations in work context and characteristics, the results of this study demonstrate that Hurtt’s (2010) professional scepticism scale can be applied. By providing accounting students in universities with an illustration of professional scepticism, the results of this study contribute to the body of accounting literature. This study aims to establish benchmarks for Malaysian universities to use in assessing the degree of professional scepticism exhibited by their accounting students; as a result, it will support efforts to mitigate this scepticism prior to graduation. This study’s findings may help Malaysia become a high-income nation by producing high-quality accounting graduates. The professional scepticism competency model proposed in this study will benefit the Malaysian Ministry of Higher Education and universities that provide undergraduate accounting degrees, improving accounting students in Malaysia.